Augmented Reality Green Training: Elevating Environmental Knowledge and Driving Pro-Environmental Behaviour Among Indonesian White-Collar Workers - Grace Herlina Maria; Iskandar Karto; Triana Ika (E3S Web of Conferences)
This study is conducted to analyse the impact of AR Green Training in enhancing environmental knowledge and further indulging in the creation of pro-environmental behaviour among white-collar workers working in Indonesia. Results from this quantitative research design distinctly engaged participants from Greater Jakarta with an augmented reality-enhanced training program, analysing data with structural equation modelling. The results show that augmented reality green training improves their knowledge about the environment significantly, and that very factor, in turn, catalyses pro-environmental behaviour. This confirms the hypothesis that environmental knowledge mediates AR training and pro-environmental behaviour. These findings underline, therefore, the utility of AR as a very strong educational tool for corporate sustainability initiatives in increasing knowledge and changing real behaviour towards environmental stewardship. The value that the study adds to the literature is that it demonstrates the effectiveness of immersive technologies in environmental education and strengthens the theoretical underpinning for TPB within a new context. The implications suggest that businesses can enhance their sustainability efforts by integrating AR into their training programs, which may significantly impact the environment. It is thus a call for further research in the sphere of long-term behavioural change and integration of new technologies in environmental training.